2018
DOI: 10.1177/0363546518755752
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of the MOON Shoulder Instability Cohort

Abstract: The MOON Shoulder Instability Study has enrolled the largest cohort of patients undergoing shoulder stabilization to date. Anterior instability is most common among shoulder instability patients, and most patients undergoing shoulder stabilization are in their early 20s or younger. The results of this study provide important epidemiological information for patients undergoing shoulder stabilization surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 23 publications
0
64
1
2
Order By: Relevance
“…The MOON Shoulder Instability study is an institutional review board-approved, multicenter prospective cohort of patients undergoing operative treatment for shoulder instability. The epidemiology of the cohort has previously been described by Kraeutler et al 11 Patients were prospectively enrolled by 26 sports medicine or shoulder fellowship-trained surgeons in 9 private and academic groups across the United States. Baseline demographic characteristics, PRO scores, physical examination data, and preoperative imaging were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MOON Shoulder Instability study is an institutional review board-approved, multicenter prospective cohort of patients undergoing operative treatment for shoulder instability. The epidemiology of the cohort has previously been described by Kraeutler et al 11 Patients were prospectively enrolled by 26 sports medicine or shoulder fellowship-trained surgeons in 9 private and academic groups across the United States. Baseline demographic characteristics, PRO scores, physical examination data, and preoperative imaging were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Although male patients have been shown to constitute approximately 80% of patients undergoing surgery for shoulder instability, female patients still account for a significant number of surgical procedures owing to the high frequency of instability in the population. 11 The high rate of injury in active patients demonstrates the need for further understanding of sex-related differences in shoulder instability.…”
mentioning
confidence: 99%
“…The authors found a 2:1 ratio of shoulder instability events during football compared with injuries during basketball. 22 RTP after shoulder instability has been evaluated in various high school, collegiate, and professional sports. Owens et al found that 45% of collegiate athletes who experienced a shoulder instability event missed greater than 10 days before returning to sport.…”
Section: Discussionmentioning
confidence: 99%
“…Our research collaborative comprises 26 sports medicine or shoulder fellowship-trained surgeons from 10 academic and private groups throughout the United States, as previously described. 6,7,29 This prospective cohort study enrolled patients undergoing surgical treatment for shoulder instability. Baseline demographic data, patient-reported metrics, physician examination data, and surgical data were collected.…”
Section: Methodsmentioning
confidence: 99%